Taṭwīr al-Mawād at-Taʿlīmiyyah fī al-Insyā’ li ‘l-Faṣli ats-Tsānī bi Kulliyyati al-Muʿallimāt al-Islāmiyyah Maʿhadi al-Īmān al-Islāmiy li ‘l-Banāt Ponorogo - Huwaida, Hasna (Universitas Negeri Malang, 2023)
The development of teaching materials is needed in order to improve learning in schools. Specifically, Arabic instruction at modern Islamic Boarding Schools in Indonesia. The Islamic Boarding School al-Īmān for Girls Ponorogo is one of the Islamic Boarding Schools that requires the development of Arabic teaching materials. The pesantren has attempted to present teaching materials for learning material Insyā’ that are consistent with its learning objectives, which have existed since the pesantren’s inception. However, the author found flaws in the teaching materials for the second grade after the observation. Therefore, the author hopes to be able to carry out the development of insyā’ teaching materials for the second grade, namely by presenting new teaching materials that are in accordance with the needs of second-grade students at the Islamic Boarding School al-Īmān. This research will try to answer two questions: what is the description of the teaching material in the book Insyā’ that is suitable for second-grade students at the Islamic Boarding School al-Īmān? And how effective is the teaching material for second-grade students at the Islamic Boarding School al-Īmān? This research is a research and development project, so the results will be analyzed through pre- and post-testing. The results of this study showed that the t-test was 8,844 larger than the t-test table of 2.02. This indicates that there is a difference between the pre-test and post-test scores, and the new teaching materials are effective in teaching insyā’ for the second grade at the Islamic Boarding School al-Īmān and have the potential to improve students’s insyā’ ability.